Total anomalous pulmonary venous connection masking an aortopulmonary window: A rare combination of defects - Shyamajit Samaddar; Dheeraj Bhatt; Munish Guleria; Dinesh Kumar Yadav; Anubhav Gupta (Wolters Kluwer Medknow Publications, 2018)
The association of aortopulmonary (AP) window with total anomalous pulmonary venous connection (TAPVC) has so far not been reported. We report a unique case of an 8-month-old child who presented with congestive cardiac failure and severe pulmonary arterial hypertension. Initial echocardiography revealed supracardiac TAPVC. Cardiac computed tomography showed the presence of Type I AP window along with the TAPVC. In the presence of severe pulmonary hypertension and dilated right ventricle, AP window may easily be missed if not actively looked for.